2016
DOI: 10.1007/s11096-016-0363-9
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and perceptions of the risks of non-steroidal anti-inflammatory drugs among orthopaedic patients in Thailand

Abstract: Background There is a high incidence of adverse effects from non-steroidal antiinflammatory drugs (NSAIDs) in Thailand, but patients' perceptions and knowledge of NSAID risks is unknown. Objective This study aims to assess patients' perceptions and knowledge of NSAID risks and factors affecting them. Setting University hospital in North-East of Thailand. Method A Cross-sectional study conducted over 4 months, using a self-administered questionnaire. Patients prescribed NSAIDs for at least one month duration fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 26 publications
3
25
0
Order By: Relevance
“…This practice may lead the public to believe that selective NSAIDs are better and safer to use. Clearly type of NSAID was a factor affecting other aspects of information provision, again confirming some of our survey results . CV side effects were only mentioned by a few participants in relation to selective NSAIDs and not with non‐selective drugs, despite similar risks .…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…This practice may lead the public to believe that selective NSAIDs are better and safer to use. Clearly type of NSAID was a factor affecting other aspects of information provision, again confirming some of our survey results . CV side effects were only mentioned by a few participants in relation to selective NSAIDs and not with non‐selective drugs, despite similar risks .…”
Section: Discussionsupporting
confidence: 87%
“…[19] Patients on the other hand have indicated that, while the majority receive information about how to use NSAIDs and their indication, fewer than half report receiving information about side effects and they perceive the risks of NSAIDs as generally low. [20] The findings from this survey do, however, concur with those of health professionals, in that attitudes towards receiving written information in the form of PILs were positive. [21] Such leaflets are not, however, widely available in Thailand, despite evidence that they can improve patient knowledge of medicines.…”
Section: Introductionsupporting
confidence: 67%
See 3 more Smart Citations